Teenage zombies - Warren, Jerry, 1925-1988; Sullivan, Don (Donald E.) (GBM Productions, 1960)
A group of teenagers becomes stranded upon an island, through the manipulations of a foreign scientist conducting experiments on the remote isle. It seems the scientist is trying to develop a nerve gas, which will change its victims into easily controlled zombies. Our teens hope of surviving rests with their friends and the sheriff, who have come to the island in search of the missing youths.